Konsep in-between space dalam arsitektur vernakular di Indonesia: kajian content analysis - Parmonangan Manurung; Diananta (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2021)
Space and architecture are two interrelated and encompassing concepts. However, space has a broad meaning in terms of location, privacy, and function such that the relationship between two spaces creates a different atmosphere and impression. A lot of studies have been conducted on space but there is no much focus on the concept of 'in-between space'. This research was, therefore, aimed at exploring in-between space in order to create a clear understanding and identify its concept in Batak Toba vernacular architecture. A content analysis method was adopted and this involves analyzing texts and images related to in-between space and Batak Toba architecture. The results showed the concept as an overlap created by two spaces in order to feel the atmosphere of both simultaneously. It was also discovered not to be a definitive space but found in the Batak Toba architecture to create a relationship between privacy, function, and environment. This means it is a key feature of the architecture and also expected to be a fundamental element in the modern Toba Batak architecture. These results are expected to serve as the basis for further in-depth research and to be applied in other ethnic architectures.